Pengaruh E-wallet Terhadap Perilaku Konsumtif Generasi Z di Kalangan Mahasiswa - Putri Kesuma Wardani; Irwan Padli Nasution; Suci Sundari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The use of e-wallets can increase consumptive behavior in Gen Z students because of the ease of transactions and promotions offered. E-wallets make shopping easier and more impulsive, increasing the possibility of unplanned spending. The development of digital technology has encouraged the ease of non-cash transactions through various e-wallet platforms such as OVO, DANA, GOPAY, SHOPEEPAY and others. Generation Z as a modern digital generation is an active user of this service, which is suspected to affect their consumption patterns. This study uses a quantitative approach with a survey method on students using e-wallets. The data was analyzed using regression techniques to see the relationship between the intensity of e-wallet use and the level of consumptive behavior.